Menelisik Peran Mediasi Family Support dan Moderasi Persepsi Low Barier to Entry terhadap Women’s Willingness to Become Gig Worker - Istiqamah, Nurul; Nursakinah, Nursakinah; Widiartiningsih, Wanda; Aprianti, Kartin (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The presence of the gig economy tries to break through barriers for women so that women can improve their abilities and participate actively in the workforce. This research aims to analyze the influence of job characteristics through family support which is moderated by the perception of a low barrier to entry on women's willingness to become a gig worker among married women. The sample in this study was 200 married female gig workers. The data collection technique used a Likert model questionnaire which was analyzed using Partial least Square SEM to analyze the seven hypotheses proposed. The results of the research show that job characteristics have a significant direct effect on family support and women's willingness to become gig workers. Family support also has a significant direct effect on women's willingness to become gig workers. Job characteristics also have a significant indirect effect, mediated by family support, on women's willingness to become gig workers. Perception of low barrier to entry moderates the relationship between job characteristics and family support and perception of low barrier to entry moderates the relationship between family support and women's willingness to become a gig worker. However, the perception of a low barrier to entry does not moderate the relationship between job characteristics and women's willingness to become a gig worker.